Labor Market and Home Production: Are Men and Women Equal? - Regina Madalozzo; Sergio Ricardo Martins; Ludmila Shiratori (Revista Estudos Feministas, 2010)
Female labor market participation is one of the central investigation topics in feminist economics’ studies. Even after an increase in the labor market participation and the decrease in the wage gap between men and women, the latter still face great difficulties on being remunerated and promoted when compared to men. Neoclassical economic models cannot explain completely these differences without making use of strong hypothesis about individual preferences and family goals. This study has as the main objective to analyze difference on the housework participation as an influencer to different conditions in the labor market for men and women. Our results show that women still have a double work shift. Among our main conclusions, we can say that women benefit more from personal income increase than with labor market participation, because their bargain power within family increases and they can decrease their housework hours.